Avaliação da temperatura ambiente de criação e da reutilização da cama no desempenho e na qualidade da carne de frango - Diniz, Talyanne Thays [UNESP] (2013)
The aim of this study was to evaluate the authoring environment and reused of litter in microbiological and physical-chemical chicken meat. Were used 900 male chicks from one day old Cobb ®, 450 distributed in a chamber 450 and raised in conventional shed. The animals were slaughtered at 21, 35 and 42 days old. Were evaluated performance indices such as weight gain, feed conversion and feed intake, carcass yield and cuts, the physico-chemical and microbiological analysis of meat from chickens; microbiota of birds. There was the bed influences on weight gain phase of 21 days (P <0.05) 0.839 Kg 0.792 Kg new bed chicken and reused litter during 35 days (P <0.01) 1,774 Kg new bed and bedding reused 1,661 Kg. Breast yield was also influenced by the bed phases of 21 days (P <0.05) new bed 30.78% and 30.00% and reused litter with 35 days (P <0.01) 32.26% new bed chicken and 31.64% reused litter. Animals reared on reused litter were able to overcome the losses of weight gain and breast yield during 42 days with no significant difference for animals raised in new bed chicken. There were significant differences (P <0.05) in redness of breast meat chicken from animals raised in thermoneutral (2.20) and environment (2.74) at 42 days. The level of oxidation was also influenced by the temperature (P <0.01) on thermal treatment with means mda 0.230 mg mda / kg to 0.180 mg mda/Kg environment. The bed chicken influenced the shear force (P <0.01) new bed 1.38 kg/cm2 1.86 kg/cm2 and reused. The reused litter showed higher initial new microbiological contamination, but the same was not observed in the microbiota of birds. Animals reared in thermoneutral have higher microbial contamination by Enterobacteria to 42 days on average 7.6 log UFC / g, compared animals reared at room temperature (6.3 to 6.9 log UFC / g). The carcass of animals from all treatments are within recommended for microbiological contamination ...